1984
DOI: 10.1002/aja.1001690406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compound 48/80 on hepatic glycogen and glucose‐6‐phosphatase early in the diurnal cycle of the rat

Abstract: The amount and distribution of glycogen as well as the activity of glucose-6-phosphatase (G-6-Pase) in the livers of rats were analyzed by biochemical and/or histochemical techniques. During the first 5 hr of the light cycle, livers of rats were sampled prior to and 30 min following an injection of compound 48/80 or Ringer's solution. Glycogen decreased significantly in response to sampling; however, treatment with compound 48/80 provoked an additional significant decrease in hepatic glycogen. These difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…(9) It is also known that enhanced glycogenolysis in the liver of rats treated once with C48/80 is independent of the content of glycogen stored in the tissue. (10) Therefore, these findings and the above-described results allow us to suggest that, in the liver of rats with a single C48/80 treatment, H 2 O 2 generation and lipid peroxidation are enhanced following VC synthesis via GSH depletion-dependent glycogenolysis, resulting in the occurrence of oxidative damage.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…(9) It is also known that enhanced glycogenolysis in the liver of rats treated once with C48/80 is independent of the content of glycogen stored in the tissue. (10) Therefore, these findings and the above-described results allow us to suggest that, in the liver of rats with a single C48/80 treatment, H 2 O 2 generation and lipid peroxidation are enhanced following VC synthesis via GSH depletion-dependent glycogenolysis, resulting in the occurrence of oxidative damage.…”
Section: Discussionmentioning
confidence: 57%
“…(9) It has also been shown in rats treated once with C48/80 that C48/80-induced glycogenolysis in the liver is independent of the content of glycogen stored in the tissue. (10) Furthermore, it has been shown that degranulation of mast cells existing in the liver tissue of rats treated once with C48/80 is not associated with glycogen depletion in the tissue. (11) Braun et al (12) have reported that depletion of reduced glutathione (GSH) induces glycogenolysis, resulting in stimulated VC synthesis in isolated mouse hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic hypotension has been implicated as the effector of numerous compound 48/80-mediated responses, e.g., the increased release of renin from juxtaglomerular cells of the kidney (34). Hypotension and reduced perfusion also have been postulated to provoke anoxia in the liver which in turn might trigger hyperglycemia and glycogenolysis (35). However, data reported in other manuscripts suggested that glycogenolysis and hyperglycemia are independent of changes in systemic blood pressure and hepatic blood flow (14,16).…”
mentioning
confidence: 95%